-4(x2+x+2)=0

Simple and best practice solution for -4(x2+x+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x2+x+2)=0 equation:



-4(x2+x+2)=0
We add all the numbers together, and all the variables
-4(+x^2+x+2)=0
We multiply parentheses
-4x^2-4x-8=0
a = -4; b = -4; c = -8;
Δ = b2-4ac
Δ = -42-4·(-4)·(-8)
Δ = -112
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 6-(d+3)+11d=83 | | 3(d+12)-7d=8-(2d+2d | | 3(4-11)+15=-6(-x+7) | | 7+10n=53 | | -7x-20=-35 | | 22+2a-a-6=37 | | 4(5c+6)=20c+20 | | 4w=w=21 | | 12x+10+10x+60=180 | | 11z+15=-5+9z | | 3(12+q)=108 | | 4m-6-7m=18 | | 1/3z=32-4/5 | | 5+x=−11 | | 3x-2=16* | | 6x-13=4x-9 | | (2x)(8)=20 | | 64=-6n+4 | | 2x-18=4x-24 | | 7x+21+10x-3=26 | | r/10=8.5 | | 2x+18+5x–6=90 | | -18+8q=11q | | 8x+5=10/3(x)-2 | | 5x−20=3x+6 | | k/6-8=0 | | -9=4x-7 | | 6x+7x=54 | | -3/2u-6=1/3u-7/4 | | 3x-24+7=-17 | | 82+x=45 | | -10y-10-2y=-10y+10 |

Equations solver categories